PENDAMPINGAN BELAJAR DARI RUMAH BAGI ANAK KELAS 7,8,9 SMP DAN KELAS 10 SMA DIMASA PANDEMI COVID 19 DI HKBP DUREN JAYA BEKASI - Hotmaulina Sihotang; Manahan Tampubolon; Bernadetha Nadeak; Rospita A. Siregar; Cheri Surina Ita (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2021)
Community Service (PkM) at HKBP Duren Jaya is the implementation and continuation of the MoU between Universitas Kristen Indonesia (UKI) and HKBP Duren Jaya in 2020. The Covid-19 pandemic has affected all sectors including the education sector, which resulted the students were learning from home. Parents and students have been experiencing many obstacles while studying from home, so PkM has chosen topics related to the needs of the congregation. PkM aims to provide increased understanding and knowledge of learning mentoring models for parents and effective learning tactics for students in junior high school and grade 10 of high school. The PkM method is a seminar and competition to make a video model of parental assistance while the children study from home. Video assessment uses indicators by evaluators. The results of the PkM are very encouraging, as shown by the seriousness of the committee from the church to optimally manage activities by still implementing health procedures strictly, active participating the seminar by asking several questions, video models of parenting assistance while the children study at home that can be a model for parents and children. Keywords: The role of parents; effective learning; study from home